ACCLIMATION AND AGRONOMIC PERFORMANCE OF POLYPLOIDS CLONES OF ARTEMISIA ANNUA L. - Rahman, Wiguna; Hafiizh, Erwin Al; Ermayanti, Tri Muji; Rantau, Deritha Ellfy; Lelono, Arthur A. (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTSomatic cell manipulation of Artemisia annua L. was conducted by induction of polyploid plants with Colchicine and Oryzalin in order to increase level of artemisinin. Polyploid plantlets were multiplied on MS medium without plant growth regulators. After acclimation processes, plants were grown in the field for agronomic performance observation. Survival rate of plantlets was recorded. Agronomic performance of plants was observed by recording height of plants, number of branches, leaf biomass, stomatal characteristics, and artemisinin content. The results showed that survival rate of the plantlets from Colchicine and Oryzalin treatments were ranging from 13.40 to 33.33% and 11.11 to 41.67%, respectively. Growth rates of plant height and plant branching were not significantly different between diploid and tetraploid plant both from Colchicine and Oryzalin treatments, except to triploid plants from Colchicine treatment. Averages of plant height from Colchicine and Oryzalin treatments were ranging from 10.0 to 220.0 cm and from 35.0 to 186.0 cm, respectively. The averages number of branches per plant of polyploid plants from Colchicine and Oryzalin treatments were ranging from 3 to 66 and from 11 to 63, respectively. Averages of dry leaves biomass between diploid and tetraploid plant from Colchicine and Oryzalin treatments were also not significantly different. They were ranging from 12 to 64 g/plant and from 11 to 62 g/plant, respectively. However, tetraploid clones have bigger size of stomata and produced more artemisinin than the diploids.Keywords: Artemisia annua L, Colchicine, Oryzalin, Polyploids, Acclimation, Agronomic performance